ANALISIS NONLINEAR BALOK BETON PRACETAK U DENGAN METODE ELEMEN HINGGA - Hamid, Desmon
This thesis study about behavior of Beam U-Shell, analyzed by numeric by using finite element method and compared with result of study experimental Numerical method used to finish the formulas finite element at condition of linear and condition of nonlinear by applying method of transfer accretion with the algorithm nonintegrated to determine the curve of nonlinearities structure completely. In analysis, assumed by bond of between concrete with the coherent bone perfect, or do not happened the slip of between bone with the concrete. Nonlinearities materials in analysis if concrete material have experienced of crack. Modeling use the of smeared-crack approach method and in calculating influence of nonlinearities materials used by model of constitutive concrete and model the constitutive. Result of analysis show the trend of curve Load versus displacement like with the result test the experimental and curve of relation of moment versus curvature and also crack pattern presented can present the behavior and criterion of structure avalanche. Utilize to get the more result more exact suggested to evaluate the slip and constraint effect from bone.